2019
DOI: 10.3390/cancers11040579
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Imaging–Environment Interactions in Cancer Modeling

Abstract: Histopathological imaging has been routinely conducted in cancer diagnosis and recently used for modeling other cancer outcomes/phenotypes such as prognosis. Clinical/environmental factors have long been extensively used in cancer modeling. However, there is still a lack of study exploring possible interactions of histopathological imaging features and clinical/environmental risk factors in cancer modeling. In this article, we explore such a possibility and conduct both marginal and joint interaction analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The histopathological images re ect the morphological features of tumor cells and histological structure of their microenvironment, which can be in uenced by individual immune function and environment in addition to molecular changes. [14,15] For instance, a previous study [16] has found that there is a signi cant correlation between TP53 mutation in lung adenocarcinoma and pathological characteristics of tumor cells. Another study has given evidence of the correlation between ampli cations of PDGFRA, EGFR, MDM2 and speci c image features in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…The histopathological images re ect the morphological features of tumor cells and histological structure of their microenvironment, which can be in uenced by individual immune function and environment in addition to molecular changes. [14,15] For instance, a previous study [16] has found that there is a signi cant correlation between TP53 mutation in lung adenocarcinoma and pathological characteristics of tumor cells. Another study has given evidence of the correlation between ampli cations of PDGFRA, EGFR, MDM2 and speci c image features in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…The information revealed by the cancer omics profile and histopathological images is not only relatively independent but also has commonality to a certain extent. The morphological features of tumor cells and histological structure of the tumor microenvironment can be influenced by molecular changes, individual immune function, and environment (15)(16)(17). For instance, a previous study (18) has found that there is a significant correlation between the TP53 mutation and pathological characteristics of tumor cells in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies are still relatively limited. With the consideration that tumor properties can be affected by molecular changes, there have been studies modeling the relationships between imaging features and molecular changes 11,12 . Considering the cost-effectiveness and routineness of biopsy and histopathological images, imaging-based modeling, if effective, can have great potential.…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies are still relatively scarce. With the consideration that tumor properties as reflected in histopathological images can be affected by molecular changes, there have been studies modeling the relationships between imaging features and molecular changes 12,13 . Such studies are biologically well-grounded.…”
mentioning
confidence: 99%